Improvement of faculty instruction and performance through the development of a computer software in monitoring student retention and faculty attendance - Libot, Mildred Manalang (Manila : National University, 2012)
Student retention is one of the more interwoven and intricate issues of modern higher education. One of the primary questions I regularly field regarding student retention is, "How do we get people to care about the issue?" and when asked why student retention is an important issue, my thoughts automatically shift to the fact that retention can affect every aspect of higher education. At its core, the retention of college students is a complex issue, representing an interplay of personal, institutional, and societal factors, with likely associated detrimental costs and implications to all three audiences [BRUNS2000].
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of appendices -- List of figures -- List of tables -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography.
Research Method : Descriptive Method.
Includes bibliographical references.